P666 Trend of Lower gastrointestinal Endoscopy in Patients with Inflammatory Bowel Diseases: A Nationwide Population-Based Study in South Korea. (21st January 2022) - Kim, S; Lee, S; Han, K; Soh, H; Koh, S J; Lee, H J; Im, J P; Kim, J S
Abstract: Background: Endoscopy plays an essential role in the diagnosis and management of inflammatory bowel disease (IBD). Although the interval of endoscopy is important to assess the disease status of IBD, there are limited research date on the real-world use of endoscopy in patients with IBD. Therefore we aimed to evaluate the current status of lower gastrointestinal (GI) endoscopy in IBD patients. Methods: We conducted a nationwide, retrospective, observational cohort study using the Korean national health insurance claims data. The endoscopy cohort with IBD was defined as an IBD population who underwent at least one colonoscopy or sigmoidoscopy between 2010 and 2019. We evaluated the annual number of lower GI endoscopy use, including colonoscopy and sigmoidoscopy in the IBD prevalent patients. In addition, we analyzed the trend of endoscopy use stratified by year after diagnosis in the patients with newly diagnosed IBD between 2010 and 2017 and the logistic regression modeling was used to estimate odds ratios and 95% confidence intervals for endoscopy, compared with never having had endoscopy, by demographic factor and therapeutic medications used for IBD. Results: The analysis included 54, 634 IBD patients (34, 633 male and 20, 001 female), among whom 24, 577 (44.94%) underwent lower GI endoscopy. During a mean follow-up of 4 years, endoscopy was performed the most in the first year after diagnosis, and it showed a decreasing trend after that. Multivariate analysis showed that IBD patients with biologics and small molecules received more endoscopy than patients without the medication (hazard ratio [HR] 27.671, 95% confidence interval [CI] 11.296–67.783). In Crohn's disease, increased number of biologics and small molecules correlated with increased number of endoscopy (HR 1.049, 95% CI 0.981–1.122 for single biologic; HR 2.343, 95% CI 1.726–3.182 for two or more biologics). In ulcerative colitis, however, only the use of biologics and small molecules, not the number of medication, correlated with increased number of endoscopy (HR 23.26, 95% CI 9.489–57.02). IBD patients with steroid (HR 1.562, 95% CI 1.509–1.61) and 5-aminosalicylic acid (HR 1.622, 95% CI 1.537–1.711) were received more endoscopy than patients without the medication. Conclusion: Endoscopy was performed more frequently in the first one year after diagnosis with IBD. Also, this study demonstrated significant association between the use of endoscopy and the biologics/small molecules administered for IBD.